2016
DOI: 10.1016/j.ram.2016.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Aislados de Bacillus provenientes de la rizósfera de cactus incrementan la germinación y la floración en Mammillaria spp. (Cactaceae)

Abstract: Cacti are the most representative vegetation of arid zones in Mexico where rainfall is scarce, evapotranspiration is high and soil fertility is low. Plants have developed physiological strategies such as the association with microorganisms in the rhizosphere zone to increase nutrient uptake. In the present work, four bacterial isolates from the rhizosphere of Mammillaria magnimamma and Coryphantha radians were obtained and named as QAP3, QAP19, QAP22 and QAP24, and were genetically identified as belonging to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
2
0
3
Order By: Relevance
“…Fernandes-Júnior et al (2015) studied the bacterial community in Caatinga grasses and observed the presence of the Bacillus genus. Chávez-Ambriz et al (2016), also observed the occurrence of Bacillus in the cacti rhizosphere of the arid zones in Mexico where rainfall is scarce, evapotranspiration is high and soil fertility low.…”
Section: Discussionmentioning
confidence: 87%
“…Fernandes-Júnior et al (2015) studied the bacterial community in Caatinga grasses and observed the presence of the Bacillus genus. Chávez-Ambriz et al (2016), also observed the occurrence of Bacillus in the cacti rhizosphere of the arid zones in Mexico where rainfall is scarce, evapotranspiration is high and soil fertility low.…”
Section: Discussionmentioning
confidence: 87%
“…Estas características de importancia ecológica han enfocado los estudios de estas especies en su conservación, principalmente proponiendo distintas formas de propagación y cultivo in vitro. En los últimos diez años, se ha incrementado el estudio sobre la actividad biológica de algunos de los metabolitos secundarios producidos por estas plantas, así como la identificación y actividad de su microbioma (Bezerra et al, 2013;Chávez-Ambriz, Hernández-Morales, Cabrera-Luna, Luna-Martínez & Pacheco-Aguilar, 2016;Bulla et al, 2017;Eke et al, 2019;Camarena-Pozos, Flores-Núñez, López & Partida-Martínez, 2021).…”
Section: Proteobacteriaunclassified
“…De manera especíca, Posada (2017) determinó que B. subtilis produce índoles totales en una concentración de 15 µg/mL usando 500 mg/mL de L-triptófano. Para B. megaterium, Chávez et al (2016) reportaron concentraciones de 6,3 a 7,1 mg/L en medio de cultivo suplementado con 1 mg/mL de triptófano; la cepa de B. megaterium utilizada en esta investigación obtuvo un valor mayor, que fue de 8,9 mg/mL. Para B. licheniformis se han obtenido concentraciones de 35,15 µg/mL en medio de cultivo líquido con Klactato, suplementado de triptófano a 100 mg/L (Sánchez & Pérez, 2018).…”
Section: Capacidad Bacteriana De Promoción De Crecimiento Vegetal In unclassified
“…En cuanto a la solubilización de fosfatos, Tejera et al (2013) identicaron cepas de Bacillus con la capacidad de solubilizar fosfatos inorgánicos en medio NBRIP líquido, en concentraciones de fosfato soluble de 0,23 y 11,58 mg/L. Por otro lado, Chávez et al (2016) obtuvieron en su investigación concentraciones desde 26,0 hasta 134,6 mg/L de fósforo soluble cultivando cepas de Bacillus. Los valores obtenidos en este ensayo fueron de 43,2 mg/L y 41,7 mg/L para Bacillus megaterium y Bacillus lincheniomis, respectivamente.…”
Section: Capacidad Bacteriana De Promoción De Crecimiento Vegetal In unclassified